Effect of early postoperative rehabilitation with aerobic exercise on functional status and cardiac remodeling in patients after heart valve surgery - I. N. Lyapina; V. A. Shaleva; Yu. E. Teplova; S. A. Pomeshkina; O. L. Barbarash (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To develop a program for early physical rehabilitation of inpatients after heart valve surgery and to evaluate its effectiveness and safety.Material and methods. The study included 80 patients with valvular heart disease (VHD) after elective on pump valve surgery. Patients in the control group (n=47) underwent standard cardiac rehabilitation after surgery; patients of the main group (n=33) additionally, starting from the 8th day after the intervention, had 14-day treadmill training with the program selection, taking into account the results of cycle ergometry spirometry (CES). A week after the operation and at the end of the training course (median, 24 days after the operation), cardiac remodeling and functional status was assessed according to echocardiography and CE, respectively.Results. For 7 days after surgery, patients of both groups were comparable. During physical training in the main group, there were no lifethreatening cardiac arrhythmias, episodes of ischemia, desaturation, as well as intracardiac hemodynamics deterioration. With a 14-day training, CES showed a significant increase in exercise tolerance (ET) in the main group from a median of 50 to 75 W (p=0,002), peak oxygen uptake (VO2peak) from 11,7 to 13,4 ml/kg/min (p=0,001). For 24 days after surgery in the control group, there was a trend towards improvement in ET and VO2peak, but without significant changes (p=0,09/p=0,08).Conclusion. Early inhospital rehabilitation, including physical training of moderate intensity with an individual treadmill speed and incline angle, starting from day 8 after surgery, showed effectiveness and safety in the form of an increase in ET and VO2peak, while not worsening hemodynamic parameters.